2006
DOI: 10.1300/j120v46n95_05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Virtual Reference from the Users’ Perspective

Abstract: This article discusses the evaluation of virtual reference services from the user perspective. It is one outcome of a long-term research project, The Library Visit Study, which has been conducted in three phases at the University of Western Ontario for more than a decade. These studies have identified the need for, and essential components of, reference interviews and good reference behaviors. The third phase of this research focuses on the factors that make a difference to the users' satisfaction with their v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 9 publications
0
29
0
1
Order By: Relevance
“…Nilsen and Ross report that "the reference interview has almost disappeared," with only 20 percent of VRS encounters (eighty-five visits) including a reference interview, though the percentage increases to 40 percent if only chat reference and not e-mail reference is considered. 37 Analysis of 114 chat transcripts of librarians helping students with homework by Walter and Mediavilla find that only 32 percent of librarians probed the students for more information before referring them to the Live Homework Help service. 38 Marsteller and Mizzy report that "the reference interview seems to be alive and well in the brave new world of synchronous digital reference," occurring in 64 percent of 865 analyzed transcripts.…”
Section: Query Clarification In Face-toface (Ftf) Referencementioning
confidence: 99%
“…Nilsen and Ross report that "the reference interview has almost disappeared," with only 20 percent of VRS encounters (eighty-five visits) including a reference interview, though the percentage increases to 40 percent if only chat reference and not e-mail reference is considered. 37 Analysis of 114 chat transcripts of librarians helping students with homework by Walter and Mediavilla find that only 32 percent of librarians probed the students for more information before referring them to the Live Homework Help service. 38 Marsteller and Mizzy report that "the reference interview seems to be alive and well in the brave new world of synchronous digital reference," occurring in 64 percent of 865 analyzed transcripts.…”
Section: Query Clarification In Face-toface (Ftf) Referencementioning
confidence: 99%
“…In its most recent year of service, 2009/2010, the consortium received 52,071 chat questions and the number of participating information agencies increased by thirty-nine (Ask a Librarian, 2010). Similar growth in participation and use of other regional and national chat consortia has occurred (Nilsen & Ross, 2006). The growth in the numbers of participating information agencies in these consortia, the increase in the number of questions received by this consortium, and the increased geographic areas served by the various consortia highlight the importance of studying location-based questions.…”
mentioning
confidence: 80%
“…Studies have also focused on the tone of the user's voice, age, facial expressions, and nonverbal, and visual cues of understanding or frustration (Bopp & Smith, 2011;Nilsen, 2006;Ronan, 2003). Nilsen and Ross (2006) found that in virtual reference services the reference interview almost disappeared, Finally, the librarians thought that which reference service is best depends on the users and their information needs.…”
Section: Face-to-face Reference Services: Librarians' Point Of Viewmentioning
confidence: 99%